From Shamans to Healers: The Survival of an Inupiaq Eskimo Skill - Turner, Edith (Anthropologica, 2022)
This paper is based on eleven months' fieldwork among the Inupiat Eskimos of Point Hope, Alaska. The effects of missionization on Inupiaq life are discussed in the first part of the paper. The Inupiat have been fully Christianized but have retained much of their pre-Christian symbolic culture. The second and focal part of the paper, an essay in the "anthropology of experience," describes the author's observation of and participation in contemporary tribal healing as practiced in Point Hope.